MEKANISME PEMBERIAN FASILITAS PEMBEBASAN PAJAK BUMI DAN BANGUNAN BAGI PENSIUNAN APARATUR SIPIL NEGARA: Mechanism for Granting Land and Building Tax Exemption Facilities for State Civil Apparatus Retirees - Cindy Lauddini Cahyadi; Januardo Sulung Partogi Sihombing (Reformasi Hukum Trisakti, 2026)
Jakarta Governor Regulation Number 16 of 2024 regulates Rural and Urban Land and Building Tax (PBB-P2) exemption for retired Civil Servants as social protection for limited-income groups. This research analyzes requirements for retired civil servants to obtain PBB-P2 exemption and policy implementation mechanisms. The research employs normative juridical approach with descriptive nature, examining legislation strengthened by interviews with Regional Revenue Agency officials and retired civil servants. Findings indicate exemption requirements include identity documents, tax object ownership proof with maximum 1,000 m² area, pension certificate, without tax arrears clearance requirement. Implementation faces challenges in socialization, administrative procedures, and inter-agency coordination affecting benefit delivery effectiveness. The research concludes enhanced socialization and procedural simplification are necessary to optimize social protection objectives through regional taxation instruments.